Study of the impact of organic minerals on spermatozoal gene expression in Osmanabadi bucks - S BACKIALAKSHMI; A ARANGASAMY; J SHARANYA NAIDU; J GHOSH; R BHATTA (Indian Journal of Animal Sciences, 2024)
Sperm transcripts aside from providing genetic material have an eminent role in post-fertilization events and embryonic development. The current study was carried out to study the gene expression in Osmanabadi buck (Capra hircus) supplemented with organic minerals. Organic minerals alone or in combination with different concentrations were fed to the treatment groups (T2- Zn 20 mg, T3- Zn 40 mg, T4- Zn 60 mg, T5- Cu 12.5 mg, T6- Cu 25 mg, T7- Cu 37.5 mg, T8- Zn 20 mg + Cu 12.5 mg, T9- Zn 40 mg + Cu 25 mg, T10- Zn 60 mg + Cu 37.5 mg) along with the concentration mixture and roughages; whereas control (T1) group was fed concentrate mixture and roughages. The sperm samples were processed for gene expression studies of Ras Homolog Family Member A (RHOA), Mesoderm Specific Transcript (MEST), Nucleoside diphosphate-linked moiety X motif 6 (NUDT6), Protamine 1 (PRM1), Protamine 2 (PRM2) and Heat shock protein 90 alpha family class A member 1 (HSP90AA) using qRT-PCR and the protein-protein interaction analysis was carried out through String database version 11.0. Supplementation of trace minerals has enhanced the gene expression at a significant level (P<0.05) in the supplemented groups. The expression of MEST, RHOA, and PRM1 was higher in Cu 25-supplemented groups; whereas, NUDT6 in Zn 20, PRM2 and HSP90AA in Zn 40 showed higher expressions. Osmanabadi bucks supplemented with Cu 25 mg have shown promising results in the present and earlier studies so it can be concluded that the field-level application of Cu 25 mg would lead to promising results.